Ockham on the Side of the Angels: Why a Classical Theist Shouldn't be Moved by Oppy's Argument from Simplicity. (25th June 2022) - McNabb, Tyler; DeVito, Michael
Abstract: A common argument put forth by naturalists (including the prominent philosopher Graham Oppy) in support of naturalism as a worldview over theism, is to claim that naturalism is a simpler hypothesis. Theism posits the existence of everything that naturalism does, plus the existence of a theistic realm. Thus, all things being equal, via Ockham's Razor, naturalism should be preferred to theism. In this essay, we argue that the Classical Theist need not worry about the naturalist's Simplicity argument. Specifically, we argue that, the one holding to a scholastic metaphysics (i.e., potency‐act distinction, participatory metaphysics, and existence‐in‐degree), in the end, will be the one with the simpler worldview.